Media Film untuk Meningkatkan Dimensi Beriman Bertakwa Kepada Tuhan YME dan Berakhlak Mulia pada Siswa - Ardiwinata, Emmy; Fadilah, Nurul; Indriani, Triana Putri (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Having faith, fear of God Almighty, and noble character is a student’s behavior to improve oneself to become a person who is oriented towards God so that he can apply this understanding in everday life. Phenomena that occur in the field include student’s lack of prayer, lack of discipline, lack of 3S attitude, lack of awareness of maintaining cleanliness, and lack of order during the flag ceremony. This study aimed to determine the influence of film media to increase the dimension of faith, fear of God Almighty, and noble character in MAN Tarakan. This type of research is quantitative with a design experimental approach one group pretest-posstest design. The population of this study was 197 students using purposive sampling techniques as many as 12 students. This research instrument uses a Likert scale. The data analysis technique in this study is descriptive an inferential analysis techniques with tests Wilcoxon, obtained asym itself amounting to 0.002 with a significance level (a) of 5% (0.05). so, it can be interpreted asym itself < a or 0.002 < 0.5, thus indicating that Ha is accepted with the hypothesis that there is an influence of film media to increase the dimension of faith, fear of God Almighty, and noble character in MAN Tarakan.